Method for reducing mixed crystals and recrystallization at abrupt change position of section of nickel-based single crystal superalloy
Through the expansion of the variable cross-section R angle and the adjustment shell preparation process, combined with the heat treatment process, the problems of hybrid crystals and recrystallization in nickel-based single-crystal high-temperature alloy castings are solved, and the integrity and performance of the castings are improved.
Patent Information
- Application Number
- CN202411965033.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
During the investment casting process of nickel-based single-crystalline high-temperature alloys, hybrid crystals and recrystallization at cross-sectional abrupt changes are prone to occur, affecting the integrity and performance of the casting.
By adjusting the wax mold structure and the mold shell preparation process, the radius of the variable cross-section R angle is expanded, and solid solution and aging are carried out during the heat treatment process to reduce the tendency to concentrate.
It effectively reduces the tendency of heterocrystals and recrystallization at the cross-sectional mutation of nickel-based single-crystal high-temperature alloys, and improves the integrity and performance of castings.
Smart Images

Figure CN119772103A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-temperature alloy investment casting, and in particular to a method for reducing impurity crystals and recrystallization at a sudden change in the cross section of a nickel-based single crystal high-temperature alloy. Background Art
[0002] Nickel-based high-temperature alloys have excellent creep properties, fatigue strength, good corrosion resistance and environmental stability, and are widely used in the manufacture of hot-end components of major power components in the fields of aviation, aerospace, ships, and energy. As the demand for thrust-to-weight ratio and gas efficiency of advanced aircraft engines continues to increase, their key high-temperature hot-end components need to withstand the interaction of thermal stress and centrifugal force for a long time under more severe working conditions, which puts higher requirements on the temperature bearing capacity of turbine blades. Therefore, single-crystal high-temperature alloys that eliminate the high-temperature weak structure-grain boundaries have gradually become the preferred material for the preparation of key components of advanced aircraft engines.
[0003] With the increasing complexity of the structure and size of high-temperature components, various solidification defects such as stray crystals and recrystallization are more likely to occur during the growth of single crystals, especially near the variable cross-section of the principle water-cooling plate. Due to the decrease in temperature gradient, the front of the solid-liquid interface is no longer horizontal. When solidifying to the variable cross-section, stray crystals are likely to occur. In addition, in order to ensure that the mold shell does not spark during the pouring process, the high-temperature strength of the mold shell needs to be improved, but this will result in poor yieldability. This makes it easy for stress concentration to occur near the R corner of the variable cross-section during the solidification process, and the stress concentration is greater, resulting in recrystallization after subsequent heat treatment.
[0004] The appearance of stray crystals and recrystallization affects the integrity of single crystal castings. During service, cracks are easily generated at the recrystallized grain boundaries and the interface between the recrystallized layer and the matrix material, which greatly reduces the alloy performance and causes serious consequences. Therefore, it is very important to develop a method to reduce the tendency of stray crystals and recrystallization in variable-section single crystal high-temperature alloy castings to improve the performance of high-temperature alloy castings. Summary of the invention
[0005] In view of this, the present invention provides a method for reducing impure crystals and recrystallization at the sudden change point of the cross-section of a nickel-based single crystal high-temperature alloy. The present invention effectively improves the situation in which impure crystals and recrystallization are easily generated in high-temperature alloy castings, and is particularly suitable for single crystal high-temperature alloy castings with complex structures, large sizes, and sudden interfaces.
[0006] In order to achieve the above object, the present invention mainly adopts the following technical solutions:
[0007] A method for reducing impurity crystals and recrystallization at a cross-section mutation of a nickel-based single crystal high-temperature alloy, the method comprising the following steps:
[0008] Step (1): preparing the wax mold, pressing the wax mold according to the process parameters, and after the wax mold is completely cooled, coating the R angle of the variable cross section (cross section mutation point) with a low melting point wax material to enlarge the R angle, and then assembling the wax mold after completion;
[0009] Step (2): preparing the mold shell, preparing the surface layer, transition layer and back layer of the mold shell, and finally sealing and drying the slurry. During the preparation process, furan resin is added to the back layer slurry, and wood chips are added to the back layer sanding material to improve the yieldability of the mold shell;
[0010] Step (3): Casting the casting, using the shell mold prepared in step (2) to cast the casting, reducing the pulling rate to 1.5 mm / min to 2 mm / min at 20 mm to 30 mm above and below the cross-sectional mutation point during casting, and cooling the casting after casting;
[0011] Step (4): The cooled casting assembly is placed in a vacuum heat treatment furnace with the shell as a whole for one solution treatment and two aging treatments.
[0012] Step (5): The casting group that has been heat treated is shelled and cut, and then corroded after cutting.
[0013] Finally, use professional polishing tools and R gauge to remove the enlarged R corner.
[0014] After the wax mold is pressed in step (1), the radius r is measured using an R gauge, and then a low-melting wax is applied to expand the R angle. The melting point of the applied low-melting wax is 10°C to 15°C lower than that of the wax used for the parts; the radius r' of the R angle after expansion is (1.2 to 1.5) r; the expanded R angle is also removed with the R gauge in the subsequent polishing procedure. After the wax mold is cooled, the wax mold is assembled. The wax mold should not be placed for more than 24 hours. When assembled, the casting is required to be completely perpendicular to the chassis.
[0015] Clean the assembled modules to facilitate slurry coating.
[0016] In step (2), when preparing the medium-sized shell, EC95 powder + silica sol are used as the surface layer and transition layer slurry. The composition of the surface layer slurry is EC95 powder: silica sol: wetting agent: defoaming agent = 3.5-4.0:1.0:0.003:0.01 in terms of mass ratio. The viscosity of the surface layer slurry is 40s-45s. The surface layer sanding material is 100# corundum sand. The composition of the transition layer slurry is EC95 powder: silica sol: wetting agent: defoaming agent = 2.5-3.0:1.0:0.003:0.003 in terms of mass ratio. The viscosity of the transition layer slurry is 30s-35s. The transition layer sanding material is 60# corundum sand.
[0017] The composition of the back layer slurry is EC95 powder: silica sol: furan resin: wetting agent: defoaming agent = 1.5-2.0: 1.0: 0.03-0.05: 0.003: 0.003 in terms of mass ratio; the viscosity of the back layer slurry is 15s-20s. When preparing the back layer slurry, first add the silica sol required by mass ratio, then add 3%-5% furan resin by mass of the silica sol, stir the silica sol and furan resin evenly at a stirring speed of 280-350 rpm, then slowly add EC95 powder while stirring, and after the addition of EC95 powder is completed, fully stir the slurry for 24h-48h; the back layer sanding material is 24# corundum sand mixed with sawdust, and the amount of sawdust added is 0.2%-0.3% of the mass content of the corundum sand. The addition of sawdust can increase the porosity of the shell, thereby improving the yield of the shell and reducing the stress concentration during the solidification and shrinkage of the casting. The addition of furan resin can improve the adhesion of the coating, ensure the close combination of sawdust and slurry, and thus improve the shell strength. The back layer is coated with 4 layers in total. After the last layer of the back layer is completely dry, the slurry is sealed, that is, another layer of back layer slurry is applied, but no sanding is performed, and finally the final drying is carried out, and the final drying time is 48h to 60h.
[0018] Step (3) is to pour the casting after the shell is prepared. During pouring, the pulling rate is reduced to 1.5 mm / min to 2 mm / min in the part between 20 mm to 30 mm below the variable cross-section and 20 mm to 30 mm above the variable cross-section, so that the front edge of the solid-liquid interface becomes horizontal and the tendency of impurity crystals is reduced. The pulling rate of other parts of the casting is 3-5 mm / min, and the pouring temperature is 1550°C ± 10°C.
[0019] After the casting is completed in step (4) and the casting group is cooled, the casting group is placed in a vacuum heat treatment furnace with a shell for solution treatment and aging treatment to avoid bumping and plastic deformation of the casting during transportation and cutting, which increases the tendency of recrystallization. When the casting group is placed in the heat treatment furnace, the pouring head needs to be inserted into the molybdenum frame dedicated to heat treatment, and the part body must not contact the molybdenum frame.
[0020] The heat treatment process in step (4) is one solution treatment plus two aging treatments. The heat treatment is carried out in a vacuum high-pressure gas quenching furnace with argon cooling. The solution treatment temperature is 1300°C ± 10°C and the solution treatment time is 240min ± 10min. The first aging treatment temperature is 1080°C ± 10°C and the holding time is 360min ± 10min. The second aging treatment temperature is 870°C ± 10°C and the holding time is 1440min ± 10min.
[0021] After the heat treatment is completed, use a hammer to knock on the pouring riser to clean the shell, and then cut the casting. After cutting, perform corrosion treatment, observe the conditions of impurities and recrystallization, and finally use a wind grinder with an R gauge to polish and remove the enlarged R angle.
[0022] The etching solution used for the etching treatment of the casting group in step (5) is FeCl 3 、HCL、HNO 3 and H 2 O composition of FeCl 3 Acidic solution, in which FeCl 3 The mass volume concentration of HCL and HNO is 0.11-0.13 g / mL. 3 and H 2 The volume ratio of O is 20-23:1:5-6, the corrosion temperature is 60℃±5℃, and the corrosion time is 5min±1min.
[0023] The present invention provides a method for preparing a variable cross-section nickel-based single crystal high-temperature alloy casting, the design concept of which is to reduce the tendency of stress concentration by changing the structure of the parts that are prone to stress concentration and adjusting the shell making process to improve the yield of the mold shell; further, the casting assembly is heat treated with the shell to reduce the tendency of plastic deformation during transportation, shell cleaning and cutting; finally, the local pulling rate is reduced to make the front of the solid-liquid interface horizontal. The present invention solves the recrystallization and stray crystal problems of variable cross-section castings with complex structures by adjusting the wax mold structure, shell making process, heat treatment method and crystal pulling speed. The method for preparing a variable cross-section nickel-based single crystal high-temperature alloy casting provided by the present invention is simple to operate, easy to implement, and reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the structure of the nickel-based single crystal high-temperature alloy casting with a sudden cross-section prepared in Example 1.
[0025] Figure 2 This is the single crystal integrity of the casting in Example 1.
[0026] Figure 3 (a), (b), and (c) are the impurity crystal conditions of the castings in Comparative Examples 1, 2, and 3, respectively.
[0027] Figure 4 (a), (b), and (c) are the recrystallization conditions of the castings in Comparative Examples 1, 2, and 3, respectively. DETAILED DESCRIPTION
[0028] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation method, structure, characteristics and effects of the present invention application are described in detail below in combination with the accompanying drawings and embodiments.
[0029] In a specific implementation process, the method of reducing the impurity crystals and recrystallization at the cross-section mutation of the nickel-based single crystal high-temperature alloy of the present invention comprises the following steps:
[0030] Step (1) wax mold preparation: the wax mold is pressed according to the process parameters. After the wax mold is completely cooled, the variable cross-section transition R corner is coated with low melting point wax material to expand the R corner radius. After completion, the wax mold is assembled.
[0031] Step (2): preparing the mold shell, preparing the surface layer, transition layer and back layer of the mold shell, and finally sealing and drying the slurry. During the preparation process, furan resin is added to the back layer slurry, and at the same time, an appropriate amount of sawdust is added to the back layer sanding material to improve the yieldability of the mold shell.
[0032] Step (3) casting: Use the shell mold prepared in step (2) to cast the casting, and reduce the pulling rate to 1.5 mm / min to 2 mm / min at 20 mm to 30 mm above and below the cross-sectional mutation point during casting, and cool the casting after casting is completed;
[0033] Step (4): The cooled casting assembly is placed in a vacuum heat treatment furnace with the shell as a whole for one solution treatment and two aging treatments.
[0034] Step (5): The casting group that has completed the heat treatment is shelled and cut. After cutting, it is corroded to observe the impurity crystals and recrystallization.
[0035] Finally, the casting described in step (5) is used to remove the enlarged R corner portion using a professional polishing tool and an R gauge.
[0036] Below, the present invention is further described in detail through examples and comparative examples.
[0037] Example 1
[0038] This embodiment prepares a nickel-based single crystal high-temperature alloy casting with a sudden cross section (such as Figure 1 As shown), the preparation method thereof adopts the method of reducing the impurity crystal and recrystallization at the cross-section mutation of the nickel-based single crystal high-temperature alloy in the present invention,
[0039] First, the wax mold is pressed according to the process parameters. The wax material is F28 type part wax with a melting point of about 70℃. After pressing, it is cooled for 30 minutes. Paramelt low-melting wax is used to expand the R angle at the R angle of the variable section transition. The melting point of the applied paramelt low-melting wax is 57℃. When coating, the R angle radius (r) is measured using an R gauge. After measurement, r is 3mm, and the R angle radius r' after expansion is 3.5mm. The expanded R angle is also removed with the R gauge in the subsequent polishing and repair procedures. After coating, the wax mold is assembled. The casting is required to be completely perpendicular to the chassis during assembly. The chassis diameter is 145mm, and there are 4 parts in each group. The assembled module is cleaned to facilitate the slurry coating. The cleaning time is 5 minutes, and it is dried for use.
[0040] Shell preparation: the mold is coated with slurry, sanded and dried to prepare the surface layer, transition layer and back layer of the shell, and finally the shell is sealed and dried to obtain the shell;
[0041] The first layer is prepared by immersing the module into the surface layer slurry for slurry coating. The composition of the surface layer slurry is EC95 powder: silica sol: wetting agent: defoaming agent = 3.8:1.0:0.003:0.01 by mass ratio. The viscosity of the surface layer slurry is 45s. Then the slurry coated module is placed in a sand spraying machine for sanding. The sanding material is 100# corundum sand. The surface layer drying time is 4h; the drying temperature is 23±2℃; the drying humidity is 70±10%RH.
[0042] Preparation of the second transition layer: immerse the module in the transition layer slurry for slurry coating. The composition of the transition layer slurry is EC95 powder: silica sol: wetting agent: defoaming agent = 3.0:1.0:0.003:0.003 in mass ratio. The viscosity of the transition layer slurry is 35s. Then put the slurry coated module into a sand spraying machine for sanding. The sanding material is 60# corundum sand. The drying time is 4h; the drying temperature is 23±2℃; the drying humidity is 70±10%RH. Preparation of the 3rd to 6th back layers, immersing the module in the transition layer slurry for slurry coating, the composition of the back layer slurry is, by mass ratio, EC95 powder: silica sol: furan resin: wetting agent: defoaming agent = 1.8:1:0.05:0.003:0.003, the viscosity of the back layer slurry is 20s, and then the slurry coated module is placed in a sand spraying machine for sanding, the back layer sanding material is 24# corundum sand mixed with sawdust, the sawdust addition amount is 0.3% of the mass content of 24# corundum sand, the particle size of the sawdust is 0.7mm, the drying time is 6h, the drying temperature is 23±2℃, and the drying humidity is 50±10%RH. Repeat the above-mentioned back layer slurry coating, sanding, and drying process 3 times, and apply 4 layers of the back layer in total. After the last layer of the back layer is completely dried, it is sealed, that is, another layer of back layer slurry is coated, but no sanding is performed, and finally the final drying is performed. The final drying time is 48 hours. After the final drying is completed, dewaxing and baking are performed. The dewaxing temperature is 170℃, the dewaxing time is 15min, and the dewaxing pressure is 8.2bar; the baking temperature is 950℃, and the baking time is 2h. After baking, it is cooled to room temperature with the furnace to obtain the required shell. Then use methylene blue + alcohol solution to conduct a leak test on the prepared shell, a total of 5 groups, of which one group has slight leakage in some positions, but it does not affect the casting after repair. The remaining shells have no leakage, and the qualified shells are ready for the next step of casting.
[0043] After the shell is prepared, a vacuum induction melting furnace is used for casting. The master alloy used for casting is DD98M nickel-based single crystal high-temperature alloy, and the weight of the material used for casting is 2.7kg; the refining temperature is 1580℃; the pouring temperature is 1550℃; during pouring, the pulling rate is reduced to 2mm / min in the part between 25mm below the variable section and 30mm above the variable section. The specific crystal pulling process is 5mm / min for the first section, and the first section crystal pulling position is 55mm; the second section pulling rate is 3mm / min, and the second section crystal pulling position is 55-200mm; the third section pulling rate is 2mm / min, and the third section crystal pulling position is 200-255mm. By reducing the crystal pulling speed near the variable section, the front of the solid-liquid interface becomes horizontal, reducing the tendency of impurity crystals.
[0044] After pouring is completed and the casting group is air-cooled for 5 hours, the casting group is placed in a vacuum heat treatment furnace with a shell for heat treatment to avoid bumping and plastic deformation of the casting during transportation and cutting, which increases the tendency of recrystallization. When the casting assembly is placed in the heat treatment furnace, the pouring riser needs to be inserted into the molybdenum frame dedicated to heat treatment, and the part body must not contact the molybdenum frame. The heat treatment process is one solution treatment plus two aging treatments. A vacuum high-pressure gas quenching furnace is used for heat treatment. The vacuum high-pressure gas quenching furnace is first evacuated to below 0.1 Pa, and then the temperature is increased to a solution temperature of 1300°C at a rate of 3°C / min, and the solution treatment time is kept for 240 minutes. Then, high-purity argon is used to cool to below 300°C at a rate of 50°C / min; then the temperature is increased to 1080°C at a rate of 3°C / min for the first aging treatment, and the holding time is 360 minutes. Then, high-purity argon is used to cool to below 300°C at a rate of 50°C / min; then the temperature is increased to 870°C at a rate of 3°C / min for the second aging treatment, and the holding time is 1440 minutes. Then, high-purity argon is used to cool to room temperature at a rate of 50°C / min.
[0045] After the heat treatment is completed, the mold shell is cleaned by hammering the pouring riser and the casting is cut. The casting after cutting is heated with 120gFeCl 3 +750mlHCL+36mlHNO 3 +200mlH 2 O was used for corrosion, the temperature of the corrosion solution was 60℃, the corrosion time was 5min, and the recrystallization and stray crystals were observed after the corrosion was completed. A total of 20 castings were cast, and no recrystallization and stray crystals were found. Figure 2 As shown, after the inspection is completed, the enlarged part of R is polished and removed using an air grinder in conjunction with the R gauge to make it meet the size requirements.
[0046] Comparative Example 1
[0047] This comparative example prepares a nickel-based single crystal high-temperature alloy casting with a variable cross-section that is the same as that in Example 1. The differences between the preparation process and that in Example 1 are reflected in the following three points: first, after the wax mold is pressed, paramelt low-melting point wax is not used to change the radius of the variable cross-section R corner; second, during the preparation of the shell, furan resin is not added to the back layer slurry and sawdust is not added to the back layer sanding material; third, the crystal pulling speed during the casting process is 5 mm / min throughout the entire process; the other preparation processes are exactly the same as in Example 1.
[0048] First, the wax mold is pressed according to the process parameters. The wax material is F28 type part wax with a melting point of about 70℃. After pressing, it is completely cooled and the wax mold is assembled according to the assembly requirements. The casting is required to be completely vertical to the chassis during assembly. The chassis diameter is 145mm, and there are 4 parts in each group. The assembled module is cleaned to facilitate the slurry coating. The cleaning time is 5 minutes, and it is dried for use.
[0049] Shell preparation: the mold is coated with slurry, sanded and dried to prepare the surface layer, transition layer and back layer of the shell, and finally the shell is sealed and dried to obtain the shell;
[0050] The preparation of the first surface layer and the second transition layer is exactly the same as in Example 1. For the preparation of the third to sixth back layers, the module is immersed in the transition layer slurry for slurry coating. The composition of the back layer slurry is, by mass ratio, EC95 powder: silica sol: wetting agent: defoaming agent = 1.8:1:0.003:0.003. The viscosity of the back layer slurry is 20s. Then, the slurry coated module is placed in a sand spraying machine for sanding. The back layer sanding material is 24# corundum sand. The other processes are exactly the same as in Example 1.
[0051] After the shell is prepared, a vacuum induction melting furnace is used to cast the casting. The crystal pulling speed during the casting process is 5 mm / min, that is, the crystal pulling speed near the variable cross-section is not changed. The other processes are exactly the same as in Example 1.
[0052] The heat treatment process of the casting group (one solution treatment plus two aging treatments), shelling, cutting, corrosion and polishing of the casting group are the same as those in Example 1.
[0053] After the corrosion was completed, the recrystallization and stray crystal conditions were observed. A total of 20 castings were cast, and the recrystallization and stray crystal conditions were relatively serious. Figure 3 (a) and Figure 4 (a), 15 failed.
[0054] Comparative Example 2
[0055] This comparative example prepares a nickel-based single crystal high-temperature alloy casting with a variable cross-section similar to that of Example 1.
[0056] In the preparation process of this comparative example, only the shell preparation process (i.e., furan resin is added to the back layer slurry and sawdust is added to the back layer sanding material during the shell preparation process) is consistent with Example 1, while other preparation processes are consistent with Comparative Example 1.
[0057] After corrosion inspection, it was found that the recrystallization problem was improved and the size became smaller, but it was not completely solved. Figure 3 (b) and Figure 4 (b).
[0058] Comparative Example 3
[0059] This comparative example prepares a nickel-based single crystal high-temperature alloy casting with a variable cross-section similar to that of Example 1.
[0060] In the preparation process of this comparative example, the preparation process of the wax pattern in step (1) is the same as that in Example 1 (i.e., paramelt low-melting point wax material is used to enlarge the R angle, and the degree of R angle enlargement is consistent with that in Example 1), and the other preparation processes are consistent with those in Comparative Example 1.
[0061] After corrosion testing, it was found that the recrystallization size was smaller than that of the control sample, but the recrystallization problem still existed. Figure 3 (c) and Figure 4 (c).
Claims
1. A method for reducing impurity crystals and recrystallization at a cross-section mutation of a nickel-based single crystal high-temperature alloy, characterized in that: The method comprises the following steps: Step (1): preparing the wax mold, pressing the wax mold according to the process parameters, and after the wax mold is completely cooled, applying a low-melting-point wax material at the R corner of the variable cross-section transition to expand the R corner radius, and then assembling the wax mold after completion; Step (2): preparing the mold shell, preparing the surface layer, transition layer and back layer of the mold shell, and finally sealing and drying the slurry. During the preparation process, furan resin is added to the back layer slurry, and wood chips are added to the back layer sanding material to improve the yieldability of the mold shell; Step (3): Casting the casting, using the shell mold prepared in step (2) to cast the casting, reducing the pulling rate to 1.5 mm / min to 2 mm / min at 20 mm to 30 mm above and below the cross-sectional mutation point during casting, and cooling the casting after casting; Step (4): placing the cooled casting assembly in a vacuum heat treatment furnace with the shell as a whole for one solution treatment and two aging treatments; Step (5): The casting group that has been heat treated is shelled and cut, and after cutting, it is corroded.
2. The method according to claim 1, characterized in that The melting point of the low-melting-point wax material applied in step (1) is 10°C to 15°C lower than that of the wax material used for the parts; during coating, an R gauge is used to measure the size of the R corner radius. If the R corner radius at the original variable section is r, then the R corner radius after expansion is r'=(1.2~1.5)r;.
3. The method according to claim 1, characterized in that In step (2) of preparing the mold shell, the composition of the surface layer slurry is EC95 powder: silica sol: wetting agent: defoaming agent = 3.5-4.0:1.0:0.003:0.01 in terms of mass ratio, the viscosity of the surface layer slurry is 40s-45s, and the surface layer sanding material is 100# corundum sand.
4. The method according to claim 1, characterized in that: In step (2) of preparing the mold shell, the composition of the transition layer slurry is EC95 powder: silica sol: wetting agent: defoaming agent = 2.5-3.0:1.0:0.003:0.003 in terms of mass ratio, the viscosity of the transition layer slurry is 30s-35s, and the sanding material of the transition layer is 60# corundum sand.
5. The method according to claim 1, characterized in that In step (2), when preparing the mold shell, the composition of the back layer slurry is EC95 powder: silica sol: furan resin: wetting agent: defoaming agent = 1.5-2.0: 1.0: 0.03-0.05: 0.003: 0.003 in terms of mass ratio; the viscosity of the back layer slurry is 15s-20s, and the back layer sanding material is 24# corundum sand mixed with sawdust, wherein the amount of sawdust added is 0.2%-0.3% of the mass content of the corundum sand, and the particle size of the sawdust is 0.6-0.8mm.
6. The method according to claim 1, characterized in that In step (3), during the casting process, except for the 20 mm to 30 mm portion above and below the cross-section mutation point, the pulling rate of the other parts of the casting is 3-5 mm / min, and the casting temperature is 1550°C ± 10°C.
7. The method according to claim 1, characterized in that In step (4), the solution treatment temperature is 1300°C ± 10°C, and the solution treatment time is 240min ± 10min; the first aging treatment temperature is 1080°C ± 10°C, and the holding time is 360min ± 10min; the second aging treatment temperature is 870°C ± 10°C, and the holding time is 1440min ± 10min.
8. The method according to claim 1, characterized in that Step (4) When the cooled casting assembly is loaded into the vacuum heat treatment furnace as a whole with the shell, the pouring and rising head must be inserted into the molybdenum frame specially used for heat treatment, and the part body must not contact the molybdenum frame.
9. The method according to claim 1, characterized in that: The etching liquid used for the corrosion treatment of the casting group in step (5) is an FeCl3 acidic solution composed of FeCl3, HCL, HNO3 and H2O, wherein the mass volume concentration of FeCl3 is 0.11-0.13g / mL, the volume ratio of HCL, HNO3 and H2O is 20-23:1:5-6, the corrosion temperature is 60℃±5℃, and the corrosion time is 5min±1min.
Citation Information
Patent Citations
Manufacturing method of monocrystal high-temperature alloy working blade
CN106270392A
Composite mold shell preparation method for reducing recrystallization tendency of high-temperature single-crystal alloy casting
CN107243601A
Method for evaluating recrystallization formation tendency of spoiler column of single-crystal high-temperature alloy hollow blade
CN114544631A
Preparation method of single-crystal high-temperature alloy turbine blade
CN116833391A
Process for inhibiting mixed crystals of single crystal blade margin plate by adding feeding sheets
CN117483653A
Cited By
A method for controlling orientation deviation of a nickel-based single crystal superalloy casting
CN122605925A